Effect of Roscovitine and mifepristone on luminal breast cancer cell proliferation - Vottero, Lucía Andrea (2021)
The use of CDK2 inhibitors, such as Roscovitine (ROSCO),appears as a therapeutic alternative to overcome the acquisitionof resistance to Palbociclib in luminal breast cancer.The aim of this work was to evaluate the effect of ROSCOon cell proliferation in cells differing in their progesterone receptor(PR) isoform context. We have already demonstratedthat T47D-YB human breast cancer cells (only expressingisoform B; PRB) had increased cyclin A levels compared toT47D-YA cells (only expressing isoform A; PRA). We decidedto evaluate if cells overexpressing PRB would be moresensitive to CDK2 inhibitors than those overexpressing PRA.T47D, T47D-YA or T47D-YB cells were treated with FGF2to increase cell proliferation and then they were treated withROSCO 2 µM. All cells were similarly inhibited by ROSCO (p< 0.01) and this was accompanied by a decrease in the levelsof phospho-ERK. When FGF2-treated cells were incubatedwith ROSCO 1 µM and/or the antiprogestin mifepristone(MFP; 10 nM), only in T47D-YA cells the combined treatmentshowed significant inhibitory effects on cell proliferation thatwere stronger than those induced by the single treatments(p < 0.01). These results suggest that the levels of cyclin Aare not a biomarker of CDK2 inhibitor responsiveness. Inaddition, we show that CDK2 inhibitors may be an option forluminal breast cancer cells overexpressing PRA isoform incombination with antiprogestins.